Applying the theories of sustainable water aid - Douglas, Caleb Brazeal, author; Carlson, Ken, advisor; Vlachos, Evan, advisor; Mumme, Stephen P., committee member; Sharvelle, Sybil, committee member (Colorado State University. Libraries, 2010)
A lack of accessibility to safe water has always been one of the greatest challenges to the rural developing world. This issue has resulted in the deaths of countless millions of people, as well as the underdevelopment of many nations. The developed world has always recognized the necessity of providing water aid to these developing nations. However, this water aid has had limited success in providing sustainable water solutions and in alleviating this crisis. Recognizing this lack of effectiveness, the theories of water aid and community development have been studied and scrutinized. This has resulted in great strides in the science of providing sustainable aid to developing nations. Yet, while much has been learned about the proper theories, little increase in success has been seen in the developing world. This study seeks to determine if one of the reasons for this lack of translated success is due to a lack of summarized and unified development principles. Therefore, this thesis attempts to collect a representative sample of literature on water aid and community development and develop a singular theory for implementing water aid. This developed procedure will serve as a step-by-step guideline that covers water aid from the community selection process to the necessity of following up with the community. This thesis will then apply this developed procedure in four communities and monitor the successes and failures. Based on this analysis, observations can be made on the viability of the new standard operating procedure. If successful, perhaps this plan could be utilized by aid organizations to provide replicable results. Additionally, observations can be made on whether a lack of collated development theories is one of the reasons for a lack of success amongst water aid. All this is done with the intention of furthering the progress of water aid, with the hope of provided greater lasting success in the developing world.
Keywords: water; sustainable; aid; humanitarian; community development; Water-supply engineering -- Developing countries; Humanitarian assistance -- Developing countries; Sustainable engineering -- Developing countries